2021
DOI: 10.1007/s40201-021-00629-6
|View full text |Cite
|
Sign up to set email alerts
|

The presence of SARS-CoV-2 in raw and treated wastewater in 3 cities of Iran: Tehran, Qom and Anzali during coronavirus disease 2019 (COVID-19) outbreak

Abstract: This study aimed to identifying the presence of SARS-CoV-2 RNA in raw and treated wastewater during the COVID-19 outbreak in Tehran, Qom and Anzali cities (Iran). From three wastewater treatment plants (WWTPs), 28 treated and untreated wastewater composite samples were collected from April 4 to May 2, 2020. In this study, polyethylene glycol 6000 (PEG 6000) was used through one-step real-time quantitative reverse transcriptase-polymerase chain reaction (qRT-PCR) for identification of RNA viruses. SARS-CoV-2 RN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 66 publications
0
24
1
1
Order By: Relevance
“…Besides testing the untreated wastewater, we also quantified SARS-CoV-2 RNA in 8 samples of treated wastewater (four sampling weeks from both WWTP), which gave negative results for both plants (data not shown). This is in contrast with some recent studies that reported the detection of SARS-CoV-2 RNA by RT-qPCR in treated wastewaters and even in rivers (Nasseri et al, 2021;Rimoldi et al, 2020;Wurtzer et al, 2021Wurtzer et al, , 2020, although near the quantification limits. These findings could be important to indicate if the wastewater treatment technologies are being efficient in the removal of SARS-CoV-2 and could provide a comprehensive view on the fate of SARS-CoV-2 along the entire chain of WWTPs.…”
Section: Sars-cov-2 Detection In Liquid and Solid Wastewater Fractionscontrasting
confidence: 99%
“…Besides testing the untreated wastewater, we also quantified SARS-CoV-2 RNA in 8 samples of treated wastewater (four sampling weeks from both WWTP), which gave negative results for both plants (data not shown). This is in contrast with some recent studies that reported the detection of SARS-CoV-2 RNA by RT-qPCR in treated wastewaters and even in rivers (Nasseri et al, 2021;Rimoldi et al, 2020;Wurtzer et al, 2021Wurtzer et al, , 2020, although near the quantification limits. These findings could be important to indicate if the wastewater treatment technologies are being efficient in the removal of SARS-CoV-2 and could provide a comprehensive view on the fate of SARS-CoV-2 along the entire chain of WWTPs.…”
Section: Sars-cov-2 Detection In Liquid and Solid Wastewater Fractionscontrasting
confidence: 99%
“…The major goal of virus concentration techniques is to accomplish better recovery of viruses so that viral contagion in wastewater can be well-monitored and assessed for mitigation and prevention against virus outbreaks anticipated in future times. Both previous and latest studies have highlighted multiple methods of virus concentration such as polyethylene glycol (PEG) precipitation ( Hasan et al, 2021 ; La Rosa et al, 2020b ; Nasseri et al, 2021 ; Saththasivam et al, 2021 ), ultrafiltration and adsorption-eluting using an electronegative membrane ( Sherchan et al, 2020 ) and ultrafiltration columns, ultrafiltration over ultracentrifugation or PEG precipitation ( Baldovin et al, 2021 ) as depicted in Table 1 .…”
Section: Sars-cov-2 Rna Detection Methods In Wastewater and Wastewater-based Epidemiology (Wbe)mentioning
confidence: 99%
“…Thirty-five studies reported the importance of SARS-CoV-2 detection in the environment as a tool to monitor the spread of the virus in the community (Agrawal et al, 2021a , Ahmed et al, 2021a , Ahmed et al, 2021b , Ahmed et al, 2020a , Albastaki et al, 2021 , Arora et al, 2020 , Bertrand et al, 2021 , Carrillo-Reyes et al, 2021 , D’Aoust et al 2021a , Davó et al, 2021 , Gerrity et al, 2021 , Gonçalves et al, 2021 , Gonzalez et al, 2020 , Graham et al, 2021 , Hasan et al, 2021 , Hokajarvi et al, 2021 , Johnson et al, 2021 , Kitamura et al, 2021 , Kumar et al, 2020 , Li et al, 2021a , Medema et al, 2020 , Miyani et al, 2020 , Mlejnkova et al, 2020 , Nasseri et al, 2021 , Petala et al, 2021 , Saththasivam et al, 2021 , Sharma et al, 2021 , Sherchan et al, 2020 , Tanhaei et al, 2021 , Wang et al, 2020 , Weidhaas et al, 2021 , Westhaus 2021 , Wu et al, 2020 , Wurtzer et al, 2020 , Zhou et al, 2021 ). Some limited their analyses to the presence or absence of the virus in wastewater without attempting to link wastewater data to epidemiological findings.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, a few studies reported only on the first detection of SARS-CoV-2 in wastewater in a certain country, without examining correlations with clinical data. These studies were performed in the following countries: Bangladesh (Ahmed et al, 2021b ); Finland (Hokajarvi et al, 2021 ), Michigan (Miyani et al, 2020 ), and Tehran (Nasseri et al, 2021 ; Tanhaei et al, 2021 ). SARS-CoV-2 occurrence and trends in congregate living settings …”
Section: Resultsmentioning
confidence: 99%